Going keyless for a seamless experience: Insights from a unified hotel access control system - Lim, W.; Teh, P.; Ahmed, P.; Cheong, S.; Ling, Huo Chong; Yap, W. (Pergamon, 2018)
© 2018 Elsevier Ltd Service providers are increasingly searching for new and innovative ways of providing customers with a seamless experience in the service environment. This paper used an engineering approach to service systems development and a model of technology acceptance as a conceptual lens through which to examine hotel guests’ acceptance of a unified hotel access control system (UHACS) for seamless hotel check-in and room access. This system is the first of its kind, and this study is the first evaluation of it using two samples consisting of 100 hands-on and 120 online survey hotel guest participants. Before completing the questionnaire, hands-on survey participants were briefed and allowed to practice using the UHACS, whereas online survey participants received a flowchart that explained the concept and process of the UHACS. The data from both samples were analyzed quantitatively through partial least squares structural equation modeling and test of difference. The results showed that the ease of using and usefulness of the UHACS significantly facilitated seamless experiences in hotel check-in and room access, which in turn, significantly and positively shaped attitudes toward the UHACS, and together with its improved security features, encouraged greater intention to use the UHACS. No significant differences in evaluations were found when gender, age, and familiarity with and risk disposition to technology were considered across the two samples. The paper concludes with a discussion of the implications of the findings for theory and practice, the limitations of the study, and directions for future research.